Diagnostic accuracy of the InBios Scrub Typhus Detect™ ELISA for the detection of IgM antibodies in Chittagong, Bangladesh - Blacksell, S; Kingston, H; Tanganuchitcharnchai, A; Phanichkrivalkosil, M; Hossain, M; Hossain, A; Ghose, A; Leopold, S; Dondorp, A; Day, N; Paris, D (MDPI, 2018)
Here we estimated the accuracy of the InBios Scrub Typhus Detect™ immunoglobulin M (IgM) ELISA to determine the optimal optical density (OD) cut-off values for the diagnosis of scrub typhus. Patients with undifferentiated febrile illness from Chittagong, Bangladesh, provided samples for reference testing using (i) qPCR using the Orientia spp. 47-kDa htra gene, (ii) IFA ≥1:3200 on admission, (iii) immunofluorescence assay (IFA) ≥1:3200 on admission or 4-fold rise to ≥3200, and (iv) combination of PCR and IFA positivity. For sero-epidemiological purposes (ELISA vs. IFA ≥1:3200 on admission or 4-fold rise to ≥3200), the OD cut-off for admission samples was ≥1.25, resulting in a sensitivity (Sn) of 91.5 (95% confidence interval (95% CI: 96.8–82.5) and a specificity (Sp) of 92.4 (95% CI: 95.0–89.0), while for convalescent samples the OD cut-off was ≥1.50 with Sn of 66.0 (95% CI: 78.5–51.7) and Sp of 96.0 (95% CI: 98.3–92.3). Comparisons against comparator reference tests (ELISA vs. all tests including PCR) indicated the most appropriate cut-off OD to be within the range of 0.75–1.25. For admission samples, the best Sn/Sp compromise was at 1.25 OD (Sn 91.5%, Sp 92.4%) and for convalescent samples at 0.75 OD (Sn 69.8%, Sp 89.5%). A relatively high (stringent) diagnostic cut-off value provides increased diagnostic accuracy with high sensitivity and specificity in the majority of cases, while lowering the cut-off runs the risk of false positivity. This study underlines the need for regional assessment of new diagnostic tests according to the level of endemicity of the disease given the high levels of residual or cross-reacting antibodies in the general population.